MSMe Export Finance Go Internasional - Sri Hastutik; Sudarmiatin Sudarmiatin; Rosmiza Bidin (Eduvest - Journal of Universal Studies, 2022)
The aim is to find out the obstacles that occur to MSMEs that go International in the payment of Kendang Djimbe's export finances and their settlement. Descriptive qualitative research method. This research wants to explore something new, which is not widely known by the public, so it wants to be studied more deeply. With the aim of describing the ongoing phenomenon when the research was carried out and examining the causes and effects of constrained export finance payments. The analytical tool used is fishbone analysis (Fishbone Diagram). Research sites on SMEs "Kendang Djimbe" as a Creative Industry in Blitar. Ten respondents interviewed related to the export of “Kendang Djimbe” to foreign countries. The key informant is the exporter of “Kendang Djimbe” to China. The result of the source of the problem that is an obstacle for Kendang Djimbe MSMEs in Blitar, is the lack of understanding of knowledge about export finance towards Go International. MSMEs in solving problems in financial transactions for exports of Djimbe Kendang Crafts, knowing and having good knowledge of the payment system, choosing a goods delivery system according to the agreement, being able to calculate the export selling price correctly, knowledge of their export permits and finding the right buyer. The originality of previous researchers examining trade barriers in exports, this